A time to kill [compact disc, unabridged] - Grisham, John (Random House Audio, 2013)
In Clanton, Mississippi, two men rape a ten-year-old girl. It's horrible, and the town reacts with proper respect for the facts. Until the girl's father takes justice into his own hands with a newly acquired assault rifle. That turns Clanton inside out, and for ten days the city is a nightmare, caught in the glare of burning crosses and the crack of sniper fire. Through it all, Jake Brigance, attorney for the defense, struggles to save his client's life, and then his own!